Empowering to improve submission of claim process in local shipyard, in Malaysia - Ismail, Azman; Osman, Nor Hasni (Faculty of Science and Technology Universiti Kebangsaan Malaysia, 2016)
This paper study about struggle faces by subcontractor in submitting their work claim due to tedious processes of verification and compilation supporting document for payment process. In order to resolve this problem, the qualitative action research study method was conducted in the shipyard to propose the best solution to overcome this issue. Subcontractor need to play active roles in getting their documentation ready while Shipyard must ensure the claim is valid for payment. Empowerment as one of Business Process Reengineering(BPR) enabler together with IT-based system being chose to overcome this issue while Action Research(AR) as a method being deploy to engage the subcontractor and shipyard staff intervention to come out with more effective solution for this problem.